ONLINE LOANS THROUGH SMART CREDIT APPLICATION; A COMPARATIVE STUDY OF ISLAMIC LAW AND POSITIVE LAW - Slamet Abidin (Al-Risalah, 2021)
This article aimed to describe and analyze the comparison of the two laws, namely Islamic Law and Positive Law, regarding online loans in the Smart Credit application. This study was a literature study using a qualitative design that was the basis for library research by exploring the postulates of Islamic law and articles of positive law that were directly related to the object studied and analyzing and concluding the comparison of the two laws. The results of this study indicated that the legal requirements for online loans in the Smart Credit application was based on the provisions of Islamic Law and Civil Code. In addition, according to Islamic Law and Positive Law, the online loan mechanism through the Smart Credit application had differences, including in Islamic Law allowing online loans. However, if the loans process used usury or interest, Islamic law forbade the lender. While the Positive Law, in this case, was contained in Article 1320 of the Civil Code, which explained that if a lender has agreed to the process of terms and conditions that the Smart Credit application has made and has bound himself in the applicable provisions, whether a loan that was known to have an interest or a delay in paying would be given a fine, then the loans process was legal in the eyes of the law. This was because they have tied themselves to the online loan process, the Smart Credit application. This study implies that online loans are allowed to be used by the public. However, people must remain careful in using online loan applications that lend funds because the interest from lending these funds is very high and will result in very large losses.